MANAJEMEN ADAPTIF MADRASAH BERBASIS NILAI-NILAI PENDIDIKAN ISLAM DALAM MERESPONS FLUKTUASI - Ahd. Mujahid; Abdul Rauf (Jurnal Manajemen Pendidikan, 2026)
This study examines adaptive management practices in madrasahs grounded in Islamic educational values as a strategic response to policy, social, and institutional fluctuations. Madrasahs are increasingly required to demonstrate organizational adaptability in order to sustain educational quality amid dynamic regulatory changes, technological developments, and socio-cultural transformations. Employing a qualitative library research approach, this study analyzes relevant scholarly literature, policy documents, and classical as well as contemporary Islamic education sources to identify conceptual frameworks and adaptive strategies applicable to madrasah management. The findings indicate that adaptive madrasah management is characterized by flexibility in decision-making, participatory leadership, continuous organizational learning, and value-based governance rooted in Islamic principles such as amanah (trustworthiness), shura (consultation), ‘adl (justice), and ihsan (excellence). These values function not only as ethical foundations but also as strategic instruments that enhance institutional resilience and responsiveness to change. Furthermore, the integration of Islamic educational values into adaptive management enables madrasahs to balance modernization demands with their religious identity.